Molecular Targeting of Glioblastoma: Drug Discovery and Therapies - Bai, Ren-Yuan (2011)
Despite advances of treatment for glioblastoma multiforme (GBM), patient prognosis remains poor. Although there is growing evidence that molecular targeting may translate into better survival for GBM, current clinical data show limited impact on survival. Recent progress in GBM genomics implicate several activated pathways and numerous mutated genes. This molecular diversity may partially explain therapeutic resistance, and several approaches have been postulated to target molecular changes. Furthermore, most drugs are unable to reach effective concentrations within the tumor due to elevated intratumoral pressure, restrictive vasculature and other limiting factors. Here we describe the preclinical and clinical developments in treatment strategies of GBM. We review the current clinical trials for GBM and discuss the challenges and future directions of targeted therapies.